Study of Serum Tumor Marker Requisition Pattern in Tertiary Hospital of Nepal - Thapa, Saroj; Risal, Prabodh (Annapurna Journal of Health Sciences, 2023)
Introduction: Tumor markers are substances that may be present in higher than normal levels in the body fluids, tissue, serum, or urine of individuals with cancer. Requesting of multiple markers is rarely of use. The aim of the present study is to know the pattern of tumor marker prescription in our tertiary hospital. Methods: The medical record of common tumor marker prescription viz. Total PSA, AFP, CEA, CA-125, CA 19-9 and CA 15-3 was reviewed over a period of one year (January 2021 to December 2021). Results: A total of 1157 markers were requested from 535 patients. The most frequently prescribed marker was CA-125 and the least prescribed marker was CA 15-3. It was found that 219 (18.9%) markers were above the reference range, while 938 (81.07%) were within the reference range. Out of 535 patients, single tumor marker was prescribed for 261 (48.7%), dual markers for 49 (9.1%), triple markers for 117 (21.8%), quadruple markers for 93 (17.4%), and five or more markers for 15 (2.8%) patients. PSA was most commonly (98.47%) prescribed as a single marker, while other tumor markers were commonly prescribed in multiple pattern. The most common combination was that of CA 19.9, CA 125, and CEA in a triple prescription pattern, and AFP was added to these three markers in a quadruple combination. Conclusion: Multiple tumor marker prescription is common in our setting. This might be due to unavailability of local guidelines and regular audit. Tumor markers should be used appropriately otherwise it may have many ill consequences.